The Character and the Spatial Concepts of Cakranegara The Historical City of Indonesia as an Alternative Urban Design - Mulyadi, Lalu (Paradigma: Jurnal Kajian Budaya, 2011)
The main challenge in Indonesian urban conservation efforts is to determine how changes can meet our current needs without jeopardizing its unique character. Cakranegara, Lombok is one of the towns that have unique character and concept for its spatial organization. This research seeks to define the character of Cakranegara by outlining the spatial city concepts in relation to the physical character based on the socio-cultural and religious principles using questionnaires, mental mapping, visual survey and interviews. The results indicate that the grid pattern, settlement blocks and the positioning of the east-west temples have become the specific character of the city. Findings suggest that cosmological philosophy that emphasizes on the relationship between human and nature is used to determine the spatial organization. This relationship is observed in the placement of the three temples which symbolizes the spirit, the dwellers as the energy and the settlement territorial as the vessel. The study concludes that the basic principles of socio-cultural and the socio-religious beliefs had created the spatial concept of this historic town.